The n-Wiener Polynomials of the Cartesian Product of a Complete Graph with some Special Graphs - Ali Ali; Haveen Ahmed (Al-Rafidain Journal of Computer Sciences and Mathematics)
The n-Wiener polynomials of the Cartesian products of a complete graph Kt with another complete graph Kr, a star graph Sr, a complete bipartite graph Kr,s, a wheel Wr, and a path graph Pr are obtained in this paper. The n-diameters and the n-Wiener indices of Kt×Kr, Kt×Sr, Kt×Kr,s, Kt×Wr and Kt×Pr are also obtained.